2010
DOI: 10.1002/cbic.200900721
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of a Novel Natural Activator of p300 Histone Acetyltranferase Provides New Insights into the Modulation Mechanism of this Enzyme

Abstract: Many severe human pathologies are related to alterations of the fine balance between histone acetylation and deacetylation; because not all such diseases involve hypoacetylation, but also hyperacetylation, compounds able to enhance or repress the activities of histone acetyltransferases (HATs) could be promising therapeutic agents. We evaluated in vitro and in cell the ability of eleven natural polyisoprenylated benzophenone derivatives to modulate the HAT activity of p300/CBP, an enzyme that plays a pivotal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…SPR analyses were carried out according to our previously published procedures [22], [23]. Briefly, SPR analyses were performed using a Biacore 3000 optical biosensor equipped with research−grade CM5 sensor chips (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…SPR analyses were carried out according to our previously published procedures [22], [23]. Briefly, SPR analyses were performed using a Biacore 3000 optical biosensor equipped with research−grade CM5 sensor chips (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Thermodynamic studies using surface plasmon resonance indicated that nemorosone has high affinity towards p300 protein (0.25 μM), and this interaction is associated with a low kinetic dissociation constant (3.2×10 -4 s -1 ), suggesting a hardly dissociable complex with a stable tertiary structure. Furthermore, the major region of nemorosone, which interacts with p300, was identified as a hydroxylated enol involving C(2), C(3), and C(4) [73]. Efforts to isolate small-molecule activators using the basic backbone structure of anacardic acid are currently underway.…”
Section: Druggability Of Hat Domainsmentioning
confidence: 99%
“…Several mechanisms have been proposed to account for this action, including its ability to target the Akt/PKB signal transducer (Díaz-Carballo et al, 2008a,b) and to induce p300 histone acetyltransferase (Dal Piaz et al, 2010). Here, we provide for the first time evidence that, in addition to its toxicity on HepG2 cells, nemorosone is a potent protonophoric mitochondrial uncoupler.…”
Section: Discussionmentioning
confidence: 70%